Decolonization in Focus: A Bibliometric Analysis of Scientific Articles from 2010 to 2023 - Mahat, Dipak; Karki, Tej Bahadur; Neupane, Dasarath; Shrestha, Diwat Kumar; Shrestha, Sajeeb (Nepal Journal of Multidisciplinary Research, 2024)
Background: Decolonization refers to the process of undoing or dismantling the systems and ideologies imposed during colonialism. Recognition of colonialism's enduring impacts has increased scholarly attention to conceptualizing and advancing decolonization. Methods: A systematic literature review approach was employed to analyze existing research on decolonization from 2010 to 2023. Quantitative bibliometric methods were used to extract metrics from publications and perform statistical analyses of trends. The Scopus database provided coverage of different four subjects. Results: A total of 980 documents were analyzed from 636 sources. Key findings include steady annual increases in production, with outputs doubling from 2019 to 2020. The United States, United Kingdom, Canada and South Africa contributed the most publications. "Decolonization", "colonialism" and population-centric keywords dominated. Conclusion: Decolonization remains an important topic of interdisciplinary and global research. Future work will be conducted on a comprehensive bibliometric analysis in this field. Novelty: This study applied bibliometric techniques to provide valuable information about quantifiable trends, relationships and gaps within the extensive body of decolonization. Network and clustering analyses revealed collaborative patterns and thematic developments over time.